2006
DOI: 10.1002/bem.20279
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of the electromagnetic hypersensitivity questionnaire

Abstract: Electromagnetic hypersensitivity (EHS) syndrome is usually defined as a condition where an individual experiences adverse health effects that he or she believes is due to exposure to objects that emit electromagnetic fields. The aim of this study was to develop a questionnaire that would identify the key symptoms associated with EHS and determine how often these symptoms occur in the general population of the United Kingdom. In the pilot study, an EHS questionnaire was developed and tested. In Study 1 the EHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 12 publications
5
80
0
7
Order By: Relevance
“…In particular, many studies provided insufficient data about their participants for us to assess the type of symptoms that they normally attribute to EMF sources or the severity of these symptoms. Several studies have demonstrated that IEI-EMF is not a homogenous condition [Rubin et al, 2008;Johansson et al, 2010], yet differences between potential subgroups cannot be assessed unless individual research teams provide sufficient information about their samples using questionnaires such as those used in previous studies [e.g., Eltiti et al, 2007;Rubin et al, 2008;Johansson et al, 2010]. Ideally, the type, severity and chronicity of symptoms, EMF triggers reported as problematic, duration of ill health, and use of coping strategies such as avoidance should be assessed [Hillert et al, 1999].…”
Section: Quality Of the Original Researchmentioning
confidence: 99%
“…In particular, many studies provided insufficient data about their participants for us to assess the type of symptoms that they normally attribute to EMF sources or the severity of these symptoms. Several studies have demonstrated that IEI-EMF is not a homogenous condition [Rubin et al, 2008;Johansson et al, 2010], yet differences between potential subgroups cannot be assessed unless individual research teams provide sufficient information about their samples using questionnaires such as those used in previous studies [e.g., Eltiti et al, 2007;Rubin et al, 2008;Johansson et al, 2010]. Ideally, the type, severity and chronicity of symptoms, EMF triggers reported as problematic, duration of ill health, and use of coping strategies such as avoidance should be assessed [Hillert et al, 1999].…”
Section: Quality Of the Original Researchmentioning
confidence: 99%
“…Prior to testing all participants completed the Electromagnetic Hypersensitivity Questionnaire (EHQ) [Eltiti et al, 2007b] to assess their current state of health and whether or not they attributed symptoms to EMFs. Volunteers were included in the ''sensitive'' group if they self-reported being sensitive to EMF emissions such as those produced by base stations and mobile handsets.…”
Section: Participantsmentioning
confidence: 99%
“…There have also been anecdotal reports of flu-like symptoms attributed to TETRA base station emissions. In addition, a small sub-group within the general population report symptoms, such as difficulty in concentrating and short-term memory loss, which they attribute to exposure from these and other mobile communications frequencies such as the Global System for Mobile Communication (GSM) and Universal Mobile Telecommunications System (UMTS) [Hillert et al, 1999;Eltiti et al, 2007b]. This condition is commonly known as ''electrosensitivity'' although the World Health Organization (WHO) recommended the label, ''Idiopathic Environmental Intolerance with attribution to electromagnetic fields'' (IEI-EMF), to acknowledge the lack of a causal connection between EMFs and symptoms [Hansson Mild et al, 2006].…”
mentioning
confidence: 99%
“…This sensitivity to EMF has been termed "electromagnetic hypersensitivity" (EHS). These non-specific symptoms include dermatological symptoms (redness, tingling and burning sensations), as well as neurasthenic and vegetative symptoms (fatigue, tiredness, concentration difficulties, dizziness, nausea, heart palpitation and digestive disturbances) (Eltiti et al 2007). These symptoms are not part of any recognized syndrome.…”
Section: Introductionmentioning
confidence: 99%